2021
DOI: 10.1101/2021.09.10.459716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A well conserved archaeal B-family polymerase functions as a mismatch and lesion extender

Abstract: B-family DNA polymerases (PolBs) of different groups are widespread in Archaea and different PolBs often coexist in the same organism. Many of these PolB enzymes remain to be investigated. One of the main groups that are poorly characterized is PolB2 whose members occur in many archaea but are predicted as an inactivated form of DNA polymerase. Herein, Sulfolobus islandicus DNA polymerase 2 (Dpo2), a PolB2 enzyme was expressed in its native host and purified. Characterization of the purified enzyme revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We have recently found that Sulfolobus Dpo2, an exo − B-family DNA polymerase, is very inefficient in nucleotide incorporation, but readily extends primer termini paired to the AP lesion (Supplementary Figure 2; Feng et al, 2021). A closer examination of replication products by Dpo2 on APcontaining templates revealed that the longest product is 1 nucleotide shorter than the template strand, indicative of the occurrence of a single nucleotide omission during the TLS extension (Supplementary Figure 2).…”
Section: Dpo2 Elongates Ap-mispaired Primer Termini Via a Lesion Loop-out Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently found that Sulfolobus Dpo2, an exo − B-family DNA polymerase, is very inefficient in nucleotide incorporation, but readily extends primer termini paired to the AP lesion (Supplementary Figure 2; Feng et al, 2021). A closer examination of replication products by Dpo2 on APcontaining templates revealed that the longest product is 1 nucleotide shorter than the template strand, indicative of the occurrence of a single nucleotide omission during the TLS extension (Supplementary Figure 2).…”
Section: Dpo2 Elongates Ap-mispaired Primer Termini Via a Lesion Loop-out Mechanismmentioning
confidence: 99%
“…Sulfolobus strains were grown in SCV (0.2% sucrose, 0.2% casamino acids, 1% vitamin solution plus basic salts) or ACV media (0.2% D-arabinose, 0.2% casamino acids, 1% vitamin solution plus basic salts) at 78 • C as previously described (Peng et al, 2012). The Dpo2 (SiRe_0615) (Feng et al, 2020) and Dpo1 (SiRe_1451) expression strain (Feng et al, 2021) were constructed previously and the Dpo4 expression strain was constructed in this study.…”
Section: Sulfolobus Strains and Cell Growthmentioning
confidence: 99%
See 3 more Smart Citations